Reconsidering the life of power : ritual, body, and art in critical theory and Chinese philosophy . - Garrison, Jim, 1951- (STATE UNIV OF NEW YORK PR, 2021)
Offers a compelling intercultural perspective on body, art, self, and society.
Keywords: Philosophy, Chinese.; Aesthetics, Chinese.; Critical theory -- China.; Philosophie chinoise.; Esthétique chinoise.; Théorie critique -- Chine.; Aesthetics.; Eastern.; PHILOSOPHY.; Confucianism.; RELIGION.; Aesthetics, Chinese; Critical theory; Philosophy, Chinese; China